PENGARUH RETURN ON ASSET, DIVIDEND PAYOUT RATIO, DAN EARNING PER SHARE TERHADAP HARGA SAHAM SYARIAH PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) TAHUN 2014-2016 - Khusnah, Hidayatul; Anshori, Mohammad Yusak (JURNAL AKUNTANSI DAN MANAJEMEN, 2018)
This study aims to investigate the effect of return on assets (ROA), dividend payout ratio (DPR) and earning per share (EPS) on sharia stock price registered in Jakarta Islamic Index (JII) period 2014-2016. The hypothesis in this study was tested using multiple regression analysis with SPSS software. The results of this study there are several findings. The first finding is, return on asset (ROA) has a positive effect on sharia stock price, which shows that the greater the ROA of the company, the profit generated by company to be larger. This will increase the attractiveness of the company is increasingly in demand by investors and the impact on rising stock prices. The next finding is dividend payout ratio (DPR) has no effect on stock price, which means dividend distribu-tion does not guarantee that the company get a big profit, sometimes the company thinks the profit earned better to invest in projects that have good prospects that can increase the company’s profit, certainly with the approval of the shareholders. The last finding in this research is earning per share (EPS) has a positive effect on sharia stock price, which means that the higher EPS shows the company’s net profit is ready to be distributed to all shareholders of the company and investors will think the company is able to earn profits for the future so that many investors are willing to invest in the company until stock prices rise.